2010
DOI: 10.1021/ic100414c
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Oxygenation of a Ruthenium Dithiolate Mimics the Mixed Sulfenato/Sulfinato Donor Sets of Nitrile Hydratase and Thiocyanate Hydrolase

Abstract: The dithiolate complex (bmmp-TASN)RuPPh(3) reacts with O(2) under limiting conditions to yield the mixed sulfenato/sulfinato product (bmmp-O(3)-TASN)RuPPh(3) in 82% yield. Isotopic labeling studies confirm O(2) as the sole source of O atoms in the product complex. X-ray crystallographic studies reveal decreases in the Ru-S bond distances of 0.026(1) and 0.151(1) A for the sulfenato and sulfinato donors, respectively, and a 0.088(1) A increase in the Ru-PPh(3) bond distance upon oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 24 publications
(43 reference statements)
0
38
0
Order By: Relevance
“…The precatalysts L 1 RuPPh 3 , L 2 RuPPh 3 , and L 3 RuPPh 3 were synthesized using the established protocols as reported earlier. 18,19 The purity of each complex was confirmed using square wave voltammetry.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The precatalysts L 1 RuPPh 3 , L 2 RuPPh 3 , and L 3 RuPPh 3 were synthesized using the established protocols as reported earlier. 18,19 The purity of each complex was confirmed using square wave voltammetry.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Model studies have found stable S-oxygenates of both Fe and Co analogues as well as those of ruthenium. [39][40][41] Air-Sensitivity Studies of [FeFe]H 2 ases As [FeFe]H 2 ases are the most active of the hydrogenases for proton reduction to H 2 , it is reasonable that they should be the most air-sensitive. Thus considerable effort has been expended on understanding the source of their O 2 sensitivity, especially in the photosynthetic green algal organism Chlamydomonas reinhardtii.…”
Section: Nickel Sulfoxygenates As Models Of Oxygendamaged [Nife]h 2 Asementioning
confidence: 99%
“…The thiolato/sulfinato (2) and sulfenato/sulfinato (3) derivatives display Ru III/II couples at more positive potentials, -0.39 and -0.26 V, respectively, due to the ligand-centered oxidations. [17,18] The Ru(III) derivatives 4 -6 can be prepared by addition of ferrocenium hexafluorophosphate (FcPF 6 ) to the corresponding Ru(II) derivative.…”
Section: Textmentioning
confidence: 99%